Aplikasi Mari Belajar Untuk Anak Usia Pra Sekolah - Masniah Masniah; Dwi Mulyani; Sah Reza Pahlevi (STMIK Banjarbaru, 2023)
Preschool learning is an effort that is achieved through the provision of learning to improve physical and mental development so that children are ready to enter childhood before entering basic education. The learning process in schools today is still conventional with learning on posters ffixed to school walls about letter recognition, posters about numbers, posters about fruit, posters about animals, some wooden blocks to get to know geometric shapes used by educators who are not very diverse. This system design uses UML (Unified Modeling Language) design tools, PH and database programming languages MySQL, as well as testing based on the Blackbox Testing method. The results of this application can support the learning process in obtaining more knowledge, making learning media new in learning, adding insight into technological media, helping teaching staff, and can add to the expected cognitive development or indicators of achievement of children's abilities.Keywords: Application; Learning; Preschool Age AbstrakPembelajaran prasekolah ialah upaya yang dicapai lewat pemberian pembelajaran untuk meningkatkan perkembangan fisik serta mental supaya anak siap merambah masa kanak-kanak sebelum memasuki pendidikan dasar. Proses pembelajaran disekolah saat ini diantaranya masih bersifat konvensional dengan pembelajaran pada poster yang ditempel didinding sekolah tentang pengenalan huruf, poster mengenal angka, poster mengenal buah, poster mengenal hewan, beberapa balok kayu untuk mengenal bentuk geometri yang digunakan oleh guru pendidik tidak terlalu beragam. Desain sistem ini menggunakan tools desain UML (Unified Modelling Language), bahasa pemrograman PHP dan basis data MySQL, serta pengujian berbasis metode Blackbox Testing. Hasil dari aplikasi ini dapat menunjang proses pembelajaran dalam memperoleh pengetahuan lebih banyak, menjadikan media pembelajaran yang baru dalam belajar, menambah wawasan tentang media teknologi, membantu tenaga pengajar, dan dapat menambah perkembangan kognitif yang diharapkan atau indikator pencapaian kemampuan anak.